Bendixson criterion in impulsive systems. (12th November 2019) - Ding, Changming; Duan, Zhipeng; Pan, Shiyao
Abstract : Bendixson's condition on the nonexistence of periodic solutions for planar ordinary differential equations is extended to differential equations with impulse. Also, we use an example of predator‐prey model to illustrate our results.